The Law of Sacrifice - Norman, Ralph (2018)
When placing Hopkins in the divisive and impassioned religious and academic world of mid-Victorian Oxford, scholars have frequently drawn attention to those University tutors and senior churchmen who in different ways influenced his mental and religious development: Benjamin Jowett, Walter Pater, Henry Parry Liddon, and (more distantly, from Birmingham) John Henry Newman. In comparison, relatively little attention has been paid to Hopkins’s own undergraduate friends and contemporaries at Balliol College, or to the question of how other young men responded to the same set of religious circumstances and intellectual influences. In this study Henry Scott Holland (1847–1918) is selected to illustrate discernible Anglican parallels to particular aspects of Hopkins’s literary style and religious faith. Examining the ways Holland’s Anglicanism resembles, engages, contests, and shadows the early spirituality of Hopkins throws useful light on their overlapping academic and religious contexts. Particular attention is paid to examples of shared vocabulary, to themes from Holland’s published sermons and religious writings, which correlate to elements of Hopkins’s work, and especially to Holland’s vision of a kenotic “law of sacrifice” set in the life of the Holy Trinity. Key works such as Holland’s Logic and Life (1882) and the influential volume of Anglican essays Lux Mundi: A Series of Studies in the Religion of the Incarnation (1889) are utilized to inform a new perspective on Hopkins’s sermons and devotional writings.
Keywords: Gerard Manley Hopkins -- Henry Scott Holland -- Lux Mundi -- Victorian preaching -- Victorian Oxford -- kenosis